Identification and Validation of Cuproptosis-Related Prognostic Signature and Associated Regulatory Axis in Uterine Corpus Endometrial Carcinoma - Chen, Yun (Frontiers in Genetics, 2022)
Background: Uterine Corpus Endometrial Carcinoma (UCEC) is a common gynecological malignancy globally with high recurrence rate and mortality rate. Cuproptosis is a new type of programmed cell death involved in tumor cell proliferation and growth, angiogenesis, and metastasis. Methods: The difference in cuproptosis-related genes (CRGs) between UCEC tissues and normal tissues deposited in the TCGA database was calculated by "limma" R package. LASSO cox regression analysis was conducted to construct a prognostic cuproptosis-related signature. Kaplan-Meier analysis was conducted to compare the survival of UCEC patients. A ceRNA network was constructed identify lncRNA-miRNA-mRNA regulatory axis. qRT-PCR was performed to verify CRGs expression in UCEC. Results: The expression of FDX1, LIAS, DLAT, and CDKN2A were upregulated while the expression of LIPT1, DLD, PDHB, MTF1, and GLS were downregulated in UCEC versus normal tissues. The genetic mutation landscape of cuproptosis-related genes in UCEC were also summarized. GO and KEGG analysis revealed that these cuproptosis-related genes were enriched in TCA cycle, glycolysis, and HIF-1 signaling pathway. LASSO cox regression analysis was performed and identified a cuproptosis-related prognostic signature including these 3 prognostic biomarkers (CDKN2A, GLS and LIPT1). UCEC patients with high riskscore had a poor prognosis with an AUC of 0.782 and 0.764 in 3-year and 5-year ROC curve. Further analysis demonstrated a significant correlation between CDKN2A and pTNM stage, tumor grade, immune cell infiltration, drug sensitivity, TMB score, and MSI score. The data of validation qRT-PCR further demonstrated the upregulation of CDKN2A and the downregulation of LIPT1 and GLS in UCEC versus normal tissues. The ceRNA network was also identified lncRNA XIST/miR-125a-5p/CDKN2A regulatory axis for UCEC. Conclusion: The current study identified a cuproptosis-related prognostic signature including these 3 prognostic biomarkers (CDKN2A, GLS and LIPT1) for UCEC. The ceRNA network was also identified lncRNA XIST/miR-125a-5p/CDKN2A regulatory axis may be involved in the progression of UCEC. Further in vivo and in vitro studies should be conducted to verify these results.